2021
DOI: 10.3390/ijms23010222
|View full text |Cite
|
Sign up to set email alerts
|

Lipofuscin Granule Bisretinoid Oxidation in the Human Retinal Pigment Epithelium forms Cytotoxic Carbonyls

Abstract: Age-related macular degeneration (AMD) is the primary cause of central blindness among the elderly. AMD is associated with progressive accumulation of lipofuscin granules in retinal pigment epithelium (RPE) cells. Lipofuscin contains bisretinoid fluorophores, which are photosensitizers and are phototoxic to RPE and neuroretinal cells. In the presence of oxygen, bisretinoids are also oxidized, forming various products, consisting primarily of aldehydes and ketones, which are also potentially cytotoxic. In a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
1
21
0
2
Order By: Relevance
“…In earlier in vitro experiments [ 38 ], we demonstrated that BisRets-OX, which are formed when LGs are irradiated with visible light, have both hydrophilic and amphiphilic properties, allowing their diffusion through the LG membrane into the RPE cell cytoplasm. It was established that these products contain cytotoxic carbonyls, which can modify cellular proteins and lipids [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In earlier in vitro experiments [ 38 ], we demonstrated that BisRets-OX, which are formed when LGs are irradiated with visible light, have both hydrophilic and amphiphilic properties, allowing their diffusion through the LG membrane into the RPE cell cytoplasm. It was established that these products contain cytotoxic carbonyls, which can modify cellular proteins and lipids [ 41 ].…”
Section: Resultsmentioning
confidence: 97%
“…Thus, this experiment showed that a significant cytotoxic effect was observed not immediately after irradiation of the samples, but after some time. This suggests that, indeed, for cytotoxic hydrophilic and amphiphilic BisRets-OX [ 38 ], time is needed for the diffusion from LGs into the cytoplasm of the RPE cell and the manifestation of a damaging effect on cell structures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations